Results 1 to 2 of 2
  1. #1
    Join Date
    Apr 2009
    Posts
    1

    Functional dependecy

    Can anyone give me the link on good tutoral on functional dependency? I am stuck with following problem

    I need algortihmic poof for following
    Give a proof that the functional dependency A → B does not logically imply the functional dependency A → BC. That is, prove A → B ! |= A → BC


    thanks

  2. #2
    Join Date
    Dec 2007
    Location
    London, UK
    Posts
    741
    Lookup Armstrong's Axioms. What would the decomposition of A → Bx imply?

Posting Permissions

  • You may not post new threads
  • You may not post replies
  • You may not post attachments
  • You may not edit your posts
  •